Expression of LEF1 and TCF1 (TCF7) proteins associates with clinical progression of nasopharyngeal carcinoma. Issue 6 (27th March 2019) - Zhan, Yuting; Feng, Juan; Lu, Junmi; Xu, Lina; Wang, Weiyuan; Fan, Songqing
Abstract : Aims: Our previous study has demonstrated that β-catenin pathway was abnormally activated in nasopharyngeal carcinoma (NPC). The purposes of the present study are to investigate whether the alterations of LEF1 and TCF1 (TCF7) proteins, the important components of the canonical Wnt/β-catenin pathway, are associated with clinicopathological features and prognostic implications. Methods: We collected 391 cases of NPC, 53 non-cancerous control nasopharyngeal mucosa and 28 pairs of NPC and their matched metastases, detected expression of LEF1 and TCF1 (TCF7) proteins in these tissues by immunohistochemistry. Results: Results showed that there were significantly increased expression of both LEF1 and TCF1 (TCF7) proteins and coexpression of LEF1 and TCF1 (TCF7) in NPC than these in non-cancerous nasopharyngeal mucosa (all p<0.001), as well as LEF1 and coexpression of LEF1 and TCF1 (TCF7) in matched metastasis NPCs than these in the primary NPCs (p=0.003 and p=0.014, respectively). In addition, expression of LEF1 and the coexpression of LEF1 and TCF1 (TCF7) proteins were positively correlated with lymph node metastasis (p=0.001 and p=0.020, respectively), advanced clinical stage (p<0.003 and p=0.027, respectively) and poor survival status of patients with NPC (p<0.001 and p=0.004, respectively). Moreover, multivariate Cox regression analysis identified that the positive expression of LEF1 was the independent poor prognostic factor for overall survival of patients with NPC (p<0.001). Conclusions: The expression of LEF1 associated positively with TCF1 (TCF7) and clinical progression of NPC, and positive expression of LEF1 protein may act as valuable independent biomarker to predict poor prognosis for patients with NPC.